DIGITAL DA’WAH FOR SANTRI AS A REVITALIZATION IN SOCIAL 5.0 - Chanifah, Nur; Rohmah, Siti (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
The current development of information and communication technology has triggered a digital transformation that has changed the industrial order. If in the Industrial 4.0 era technology was only placed as a machine or tool to access information, then in the Social 5.0 era technology and its functions have been emphasized more as part of human life. Islamic boarding schools as educational institutions are currently also required to be able to accelerate and transform according to these developments. If previously the da'wah media was more conventional with a very limited reach, now it is hoped that santri can expand their da'wah by using digital media so that their contribution can reach all levels of society. This is an opportunity and a challenge for Islamic boarding schools in developing da'wah. This activity uses a personal approach by providing understanding to caregivers and administrators of the Tahfidz Al-Quran Islamic Boarding School Merjosari Lowokwaru Malang "Oemah al-Quran" about the importance of digital da'wah for students as a provision when students have graduated from the Islamic boarding school. For this reason, the UPT PKM Universitas Brawijaya community service team provided a solution by holding digital da'wah training by inviting competent resource persons in their fields. In this community service activity, the Community Service Team collaborates with preachers as well as content creators who are experts in the field of virtual preaching. Some of the digital platforms that are in digital da'wah training are Twitter, Instagram, Facebook, and Twitter. From the results of the training, some students already understand how to make da'wah material that is interesting and can be delivered in the virtual world. From the results of the evaluation carried out by the community service team, it was found that the majority of students had good enthusiasm for the material presented because awareness grew both when the material was delivered, or during the socialization process.